2016
DOI: 10.1007/s10433-016-0386-z
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference in the prevalence and socio-demographic correlates of mobility disability among older adults in Nigeria

Abstract: The aim of the current study is to examine gender differences in mobility disability among older people in Nigeria, and to explore factors associated with gender differences in mobility disability in later life. Data were used from the first (2010-2011) wave of the Nigeria General Household Survey-Panel, which included 3586 respondents aged 50 years and above. Mobility disability was assessed as self-reported difficulty in walking 100 m, walking 1 km, walking uphill, running, bending or stooping, and climbing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…with a similar gender disparity as shown in studies from other developing countries (Balogun & Guntupalli, 2016). However, the disability prevalence rate is a much lower than reported in other survey studies conducted in Bangladesh (Cherry et al, 2012;Tareque et al, 2013) as well as in international studies.…”
Section: Disability Prevalencesupporting
confidence: 80%
“…with a similar gender disparity as shown in studies from other developing countries (Balogun & Guntupalli, 2016). However, the disability prevalence rate is a much lower than reported in other survey studies conducted in Bangladesh (Cherry et al, 2012;Tareque et al, 2013) as well as in international studies.…”
Section: Disability Prevalencesupporting
confidence: 80%
“…However, in general, the elderly who lived alone (not married, divorced, or widowed), especially men, highly risked to have mobility limitation [30]. Similarly, the residence area variable in this study statistically did not affect significantly the elderly mobility limitations; and it is also in line with several previous researches [5] [8].…”
Section: Resultssupporting
confidence: 88%
“…The lack of hearing, vision, mobility, and increased risk of non-communicable diseases will appear along with the aging process [3] [4]. The mobility function plays an important role in the healthy aging, closely related to the quality of life of the elderly [5]. The mobility function usually deteriorates in old age, but in a different course, extent and speed for each individual [6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that sociodemographic variables are associated with disabilities, including age, gender, marital status, education, and economic status. Disability has been shown to be more common in females and in divorced/separated/widowed respondents, and has been positively associated with increasing age and inversely associated with education and economic status [ 28 , 29 ]. In the current study, subjects who were older at the initial diagnosis, female, who had lower educational levels had higher levels of physical disability for all chronic conditions, which was consistent with the findings of prior studies [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%